Anesthesia in High-Risk Patients (Springer International Publishing, 2018)
This book describes the approach to anesthetic and perioperative management in different categories of high-risk patient scheduled to undergo elective noncardiac surgery. Individual sections focus on patients with conditions entailing cardiac and hemodynamic risks, respiratory risks, renal and metabolic risks, neurological risks, and other forms of risk. For each condition, up-to-date guidance is provided on risk evaluation, risk stratification, and intraoperative and postoperative anesthetic management. This is the first time that such different clinical situations have been gathered together in a single textbook of anesthesiology. All of the authors are international experts with extensive clinical experience. The aim is to provide trainee anesthesiologists with clear guidance that will prove invaluable when managing a wide range of patients with serious illnesses or conditions that pose a significant anesthetic risk. The book will also serve as a valuable reference for more experienced anesthesiologists and intensivists.